Prawo nabycia nieruchomości leśnych a przekształcenie przedsiębiorcy w spółkę kapitałową na gruncie ustawy o lasach - Biędzio, Natalia (Studia Prawa Publicznego, 2025)
The article analyses the effects of transforming an entrepreneur into a capital company in the context of the right to acquire forest estates vested in the State Treasury and represented by the State Forests. This controlling institution was introduced along the lines of the solutions adopted in the context of agricultural real estate. Despite the structural similarities between Article 37a of the Act of 28 September 1991 on Forests and Article 4 of the Act of 11 April 2003 on the Shaping of the Agricultural System, their scope of application differs. The Forests Act does not provide for the acquisition right to apply to “other legal events”, such as the transformation of a sole proprietor into a capital company. This marks a clear distinction from the regulations applicable to agricultural real estate. In the article, the author analyses the construction of the entrepreneur’s transformation on the grounds of the Act of 15 September 2000 – Code of Commercial Companies, a comparative analysis of Article 37a of the Act on Forests and Article 4 of the Act on Shaping the Agricultural System, and presents the statements of doctrine and case law. In the light of the findings, the author concludes that the transformation of an entrepreneur into a capital company does not trigger the State Treasury’s right of acquisition in relation to the forest estate. This follows from the interpretation of the provisions of the Forest Act and the statements of doctrine. In addition, the application of an expansive interpretation to Article 37a of the Forest Act could lead to undue interference with the right of ownership. Such interference is not conducive to the protection of forest resources and could unnecessarily burden entrepreneurs.